The Impulsive Acceleration of a Solar Filament Eruption Associated with a B-class Flare - Xinyue Wang; Hongqiang Song; Yao Chen; Leping Li; Zhenyong Hou; Ruisheng Zheng (The Astrophysical Journal)
The eruption of magnetic flux ropes (MFRs), often taking filaments together, leads to coronal mass ejections (CMEs). Theoretical studies propose that both the resistive magnetic reconnection and the ideal instability of an MFR system can release magnetic-free energy and accelerate CMEs (i.e., MFRs or filaments) during eruptions. Observations find that the full kinematic evolution of CMEs usually undergoes three phases: the initiation phase, impulsive acceleration phase, and propagation phase. The impulsive acceleration phase often starts and ceases simultaneously with the flare onset time and peak time, respectively. This synchronization can be explained by the positive feedback relationship between the acceleration of CMEs and flare magnetic reconnection, and suggests that the reconnection has the dominant contribution to the acceleration of CMEs. It is rare to see strong evidence that supports the dominant contribution of ideal instability to the acceleration. In this paper, we report an intriguing filament eruption that occurred on 2011 May 11. Its complete acceleration is well recorded by the Atmospheric Imaging Assembly on board the Solar Dynamics Observatory. The kinematic analysis shows that the impulsive acceleration phase starts and ceases obviously earlier than the flare onset time and peak time, respectively, which means a complete asynchronization between the impulsive acceleration phase and flare rise phase, and strongly supports that the ideal instability plays a dominant role in this impulsive acceleration. Furthermore, the accompanied flare is a B-class one, also implying that the contribution of reconnection is negligible in the energy release process.